Adiponectin, IL-10 and metabolic syndrome in obese children andadolescents - Calcaterra, V.; De Amici, M.; Klersy, C.; Torre, et al., C. (Acta Biomedica Atenei Parmensis, 2009)
The metabolic syndrome (MetS) is a common basis for the development of atherogenic cardiovascular disease. Adiponectin has been demonstrated to be insulin-sensitizing and an anti-atherogenic factor and is considered a key of MetS. It was suggested that IL-10 may be involved in the inflammatory network of MetS in relation to adiponectin. We examined the relationship between adiponectin, IL-10 and MetS in pediatric obese patients. MetS components were assessed in 70 severely obese and 30 non-obese children and adolescents. Serum levels of adiponectin and IL-10 were measured in these subjects. Serum adiponectin levels were significantly lower (p